Strategi Komunikasi Persuasif Pada Episode 'Bangkit Dari Kegagalan' Kanal Youtube Satu Persen - Fitri Awliyani; Zuhriah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
The development of information technology has transformed YouTube into an educational digital space, one of which is through the One Percent channel which consistently produces self-development content. This study aims to comprehensively analyze the structure of persuasive message construction and identify the integration of Aristotle's rhetorical elements in a video entitled "Motivation to Rise from Failure (Life Motivation Video)". Using a qualitative approach with a descriptive case study method, the researcher acts as the main instrument through digital observation techniques and full transcription documentation. The data analysis technique applied using the interactive model of Miles, Huberman, and Saldaña. The results of the study show that the persuasive communication strategy in the video is constructed through the systematic integration of three rhetorical elements, namely ethos (credibility of channels and educational style), pathos (emotional narrative through storytelling), and logos (rational explanation of the concept of failure psychology and its solutions). Based on the Elaboration Likelihood Model (ELM), the persuasion process is strengthened by a balanced combination of the central route (logical argument) and the peripheral route (intonation and emotion). Academically, this research contributes to the development of the literature on digital persuasive communication strategies. Practically, the results of this analysis can be a tactical guide for content creators in designing motivational content that is both scientific and communicative.